Influence of consumer perceptions of private label brands on store loyalty – evidence from Indian retailing - Sanjeevni Gangwani; Meenu Mathur; Sana Shahab (Cogent Business & Management, 2020)
In India growth of private label brands corresponds with the increasing share of organized retailing. The consumer perceptions of private label apparel brands of retail department stores have been examined by means of structural equation modelling approach. The model illustrates the influence of consumer perceptions towards private label familiarity, affective perception, perceived quality, perceived value, and perceived risk perceptions including functional risk, financial risk, and social risk perceptions on store loyalty. The study found that favourable consumer perceptions of apparel private label brands of retail department stores significantly influence the consumer to be loyal to the store. It implies that retailers wishing to boost loyalty to their store should formulate appropriate private label brand strategies so as to solicit favourable perceptions towards their store's private label offerings.
Keywords: 650; familiarity; affective perception; perceived quality; perceived value; perceived risk dimensions